2013
DOI: 10.1371/journal.pbio.1001719
|View full text |Cite
|
Sign up to set email alerts
|

ANXUR Receptor-Like Kinases Coordinate Cell Wall Integrity with Growth at the Pollen Tube Tip Via NADPH Oxidases

Abstract: Pollen tubes grow extremely rapidly to effect fertilization in plants. ANXUR receptor-like kinases facilitate this growth by linking the intracellular growth machinery of pollen tubes to the status of the extracellular matrix via H2O2 and Ca2+ signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
277
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 255 publications
(290 citation statements)
references
References 59 publications
(110 reference statements)
11
277
0
2
Order By: Relevance
“…To study the effect of the R240C mutant form further, WT plants were transformed with both MRI-CFP and MRI R240C -CFP. Previously, we reported that overexpression of ANX1 mildly inhibits pollen germination and PT growth, most likely by triggering overaccumulation of secreted CW material (6). In transgenic lines with strong expression of MRI-CFP, only a few pollen grains displayed membrane invaginations and CW accumulation (n = 31 of 444 fluorescent PTs) (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…To study the effect of the R240C mutant form further, WT plants were transformed with both MRI-CFP and MRI R240C -CFP. Previously, we reported that overexpression of ANX1 mildly inhibits pollen germination and PT growth, most likely by triggering overaccumulation of secreted CW material (6). In transgenic lines with strong expression of MRI-CFP, only a few pollen grains displayed membrane invaginations and CW accumulation (n = 31 of 444 fluorescent PTs) (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…To position MRI in the ANX1/2 signaling pathway, we tested whether overexpression of MRI and MRI R240C could rescue partially malesterile rbohH rbohJ mutant plants (6). All 32 independent T1 lines of rbohH rbohJ with MRI-CFP fluorescence remained partially sterile (e.g., for three independent T1 lines with high CFP expression, seed set was 8.5 ± 3.1, 8.8 ± 3.9, and 9.4 ± 4.2) similar to untransformed rbohH rbohJ plants (7.2 ± 2.1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Reactive oxygen species (ROS) accumulate at the tip of growing pollen tubes and 2 NADPH oxidases, respiratory burst oxidase homolog H (RbohH) and RbohJ, specifically localized in the plasma membrane of the growing tip 2 are involved in this accumulation. [2][3][4] The ROS are suggested to stimulate the plasma membrane Ca 2C -permeable channel(s) and induce Ca 2C influx into the cytoplasm. 5 The cytosolic Ca 2C rise in turn activates the ROS-producing activity of Rboh proteins by direct binding to the EF-hand motifs and by phosphorylation through the Ca 2C -dependent protein kinases, generating a positive feedback regulation that maintains the growth site to the tip during elongation (Fig.…”
Section: Ros Accumulate In the Apoplast Of Pollen Tube Tip Upon Pollimentioning
confidence: 99%